Analysis of scoring systems for primary immunodeficiency diagnosis in adult immunology clinics. (13th October 2020) - Toms, K.; Gkrania‐Klotsas, E.; Kumararatne, D.
Summary: Failure to spot the signs of primary immunodeficiency (PID) often results in delayed diagnosis. Scoring systems to identify PID exist, such as the immunodeficiency disease‐related (IDR) score. This research aims to analyse and improve the diagnostic sensitivity and specificity of the IDR scoring system in a small preselected group of adult patients referred to immunology with clinical suspicion of a PID. Records of all patients presenting for the first time to an adult immunology clinic in 2018 at Addenbrooke's Hospital, Cambridge, were scored using the unmodified IDR score and modified versions of it. Included records were searched for a subsequent diagnosis of PID, and the diagnostic sensitivity and specificity of the scoring systems were analysed. Of 400 patients, 213 were excluded: 141 due to secondary immunodeficiency, 69 due to no clinical suspicion of a PID, and hence no investigation for PID, and three due to ongoing diagnostic investigations. Of 187 included patients, 71 were found to have a clinically significant PID. The unmodified IDR score was useful in discriminating between those with and without PID. Modification of the scoring system with seven additional criteria improved the sensitivity and specificity for PID diagnosis to the greatest extent. A modified IDR score with seven additional criteria validated in adults referred to immunology with suspicion of a PID could be used clinically to aid PID diagnosis, although further validation in different patient cohorts is required before it is used in other contexts. Abstract : Our research applies a scoring system designed to identify undiagnosed primary immunodeficiency in a population of adults presenting to an immunology clinic. Key findings include that modification of the scoring system with additional criteria may improve its sensitivity and specificity in identifying those with primary immunodeficiency based on their clinical history.